A Study of Determinants of Intellectual Capital Performance in Firms: The Vietnamese Case - Dinh Nguyen, Phan; To, Thi Nhat Minh (Organizations and Markets in Emerging Economies, 2024)
This research examines determinants of intellectual capital (IC) performance in firms in Vietnam during the period 2007–2022 through employing the system generalized method of moments (SGMM) and the structural equation model (SEM). Our findings show that market capitalization (MC), sales growth, profitability, leverage, FDI, inflation and GDP significantly affect IC performance. Global crises influence it negatively and have a moderating effect on IC performance through MC, sales growth, and return on asset. This research contributes to the existing literature by examining IC performance with a consideration of the effect of the global crises and analyzing the moderating effect of the crises on IC performance. It also contributes to the literature by adding and examining the effect of MC on IC performance.